2021
DOI: 10.2147/ndt.s290692
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of TCM Constitution and Related Biomarkers for Mild Cognitive Impairment

Abstract: The incidence of Alzheimer's disease is on the rise, early detection of cognitive impairment of the elderly is very important. In traditional Chinese medicine, constitution is related to the susceptibility of the human body to diseases. Based on the theory of constitution of traditional Chinese medicine (TCM), the human population can be classified into 9 constitutions. However, little is known about the characteristics of medical constitution and related biomarkers in subjects with mild cognitive impairment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…TCM describes a state of health maintained by a balance of energy or Qi in the body ( Xutian et al, 2009 ). According to TCM, Qi-Deficiency is a common feature in older adults with MCI ( Deng et al, 2021 ). Acupressure treatment can stimulate the related meridians and reproduce an effect usually defined as “De Qi” to correct the imbalance of Qi in the body ( Smith et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…TCM describes a state of health maintained by a balance of energy or Qi in the body ( Xutian et al, 2009 ). According to TCM, Qi-Deficiency is a common feature in older adults with MCI ( Deng et al, 2021 ). Acupressure treatment can stimulate the related meridians and reproduce an effect usually defined as “De Qi” to correct the imbalance of Qi in the body ( Smith et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sleep quality is inversely proportional to the score [ 9 ]. ③ TCM constitution [ 10 ] adopts the Classification and Determination of Constitution in TCM, which consists of nine parts: balanced constitution, inherited special constitution, Yin deficiency constitution, Yang deficiency constitution, blood stasis constitution, phlegm-dampness constitution, dampness-heat constitution, Qi stagnation constitution, and Qi deficiency constitution. Each question is rated on a five-level basis, and the original score and conversion score are calculated based on a formula.…”
Section: Objects and Methodsmentioning
confidence: 99%
“…In another study of TCM constitution in 152 patients with MCI, neutral was the most frequent constitution (33.6%), followed by Qi-deficient (33.5%), Yang-deficient (21.7%), Phlegm-dampness (9.2%), and Blood-stasis (7.9%). 12 In a study of 52 mild to moderate patients with AD, liver-kidney yin deficiency was the most frequent pattern (64.8%). 36 In a randomized controlled trial of patients with mild to moderate AD, appropriate herbal medicine was prescribed according to the pattern identification of Heart Qi-deficiency, Kidney Yin-deficiency, Phlegm-dampness, and Blood stasis.…”
Section: Discussionmentioning
confidence: 98%
“…In recent studies, efforts have been made to measure the TCM or KM pattern objectively in patients with cognitive impairment. 11 , 12 Specifically, in a real-world multicenter controlled clinical study conducted in China, sequential therapy based on the evolvement of patterns (STEP) regimen was applied for patients with Alzheimer’s Disease (AD) 13 , 14 and the authors concluded that early AD initiates from kidney deficiency, and as the disease progress, phlegm-dampness, blood stasis, and fire-heat could occur pathologically. According to the sequential patterns of AD patients, herbal medicine demonstrated beneficial effects in maintaining cognitive stability in patients with AD after the 2-years of follow-up.…”
Section: Introductionmentioning
confidence: 99%